Viewer Exposure to and Perception of Political Advertisements in the 2020 Ghanaian General Election: A Study of Voters in the Ledzokuku Constituency - Manu, K. A. (University of Ghana, 2025)
This mixed-method study investigated the viewers’ exposure to and perception of political advertisements that were played during the 2020 general elections in Ghana. Using the rhetorical appeals theory, the study examined the contributions of political advertisements in voters' decision-making to vote for a particular political candidate or party during the 2020 general elections. The specific objectives of the study were to examine the nature of political advertisements voters were exposed to, find out how voters engaged with TV political advertisements, examine voters’ perceptions about the role the political advertisements played in their voting decisions, and find out whether demographic differences (gender and education level) shaped voters’ reception practices towards political advertisements during the 2020 general elections. A qualitative content analysis was employed to analyze the content of eight (8) political advertisements of the New Patriotic Party (NPP) and National Democratic Congress (NDC) that were played on television during the elections. Focus group discussion was also employed to gather data from six (6) voters after they exposed to political advertisements. Moreover, a survey was undertaken to gather data from two hundred and five (205) voters in the Ledzokuku Constituency. The study revealed that the two parties deployed all three rhetorical appeals, ethos (credibility and trustworthiness), pathos (emotional appeals to connect with voters) and logos (logical and rational arguments to support the candidates or parties) in their advertisements. The majority of the voters in the constituency engaged with the advertisements of the candidates or parties they support, induced by strong affiliations with the candidates or parties. It was also indicated that the majority of the voters were exposed to messages which they perceived to have informed their voting decisions. Educational level did not play any major role in voters' interest in messages that highlighted the policy and programme proposals of candidates or parties. In terms of gender differences, female voters were more interested in watching advertisements that showed celebrities and other people who endorsed candidates or parties than male voters.
MPhil. Communication Studies
Keywords: viewers’ exposure; political advertisements; general elections; Ghana